Sustainable Enterprise Value Creation Implementing Stakeholder Capitalism through Full ESG Integration - Samans, Richard (Springer Nature, 2022)
This Open Access book provides a practical guide to the creation of sustainable enterprise value and implementation of the principles of stakeholder capitalism for corporate boards and management teams. The authors argue that business leadership is on the threshold of a new era driven by major shifts in technology, society, political economy and climate change. They set this transition in international and historical context and outline a comprehensive leadership agenda for fully integrating environmental, social, governance (ESG) and data stewardship risks and opportunities into corporate governance, strategy, reporting and partnerships. This systematic approach is illustrated with good practices by leading companies and includes an explanation of how sustainability reporting is making the leap into formal accounting standards set by the same body that oversees international financial accounting standards and what companies should do to prepare. The book's combination of scholarly analysis and practical guidance make it a valuable resource for anyone seeking to navigate the new business context, whether from the perspective of a board director, C-suite executive, manager, policymaker, scholar or student. This is an open access book.